A distal enhancer maintaining Hoxa1 expression orchestrates retinoic acid-induced early ESCs differentiation. Issue 13 (31st May 2019) - Su, Guangsong; Guo, Dianhao; Chen, Jun; Liu, Man; Zheng, Jian; Wang, Wenbin; Zhao, Xueyuan; Yin, Qingqing; Zhang, Lei; Zhao, Zhongfang; Shi, Jiandang; Lu, Wange
Abstract: Retinoic acid (RA) induces rapid differentiation of embryonic stem cells (ESCs), partly by activating expression of the transcription factor Hoxa1, which regulates downstream target genes that promote ESCs differentiation. However, mechanisms of RA-induced Hoxa1 expression and ESCs early differentiation remain largely unknown. Here, we identify a distal enhancer interacting with the Hoxa1 locus through a long-range chromatin loop. Enhancer deletion significantly inhibited expression of RA-induced Hoxa1 and endoderm master control genes such as Gata4 and Gata6. Transcriptome analysis revealed that RA-induced early ESCs differentiation was blocked in Hoxa1 enhancer knockout cells, suggesting a requirement for the enhancer. Restoration of Hoxa1 expression partly rescued expression levels of ∼40% of genes whose expression changed following enhancer deletion, and ∼18% of promoters of those rescued genes were directly bound by Hoxa1. Our data show that a distal enhancer maintains Hoxa1 expression through long-range chromatin loop and that Hoxa1 directly regulates downstream target genes expression and then orchestrates RA-induced early differentiation of ESCs. This discovery reveals mechanisms of a novel enhancer regulating RA-induced Hoxa genes expression and early ESCs differentiation.